Coral Glynn - Cameron, Peter, 1959-; Antón, Patricia (Barcelona, España : Libros del Asteroide S.L.U., 2013)
Nursing an elderly cancer patient in an isolated English countryside manse in 1950, Coral interacts with a disgruntled housekeeper and her charge's sexually torn and war-ravaged son until a series of random events culminates in a complicated marriage.
Online resource; title from ePub title page (Digitalia, viewed March 14, 2018)
Keywords: Man-woman relationships -- Fiction; England -- Fiction; Romance fiction; Electronic books